Density Functional Theory Investigation of Intermolecular Interactions for Hydrogen-Bonded Deep Eutectic Solvents - Bauyrzhan Myrzakhmetov; Mirat Karibayev; Yuquan Wang; Almаgul Mentbayeva (Institute of Combustion Problems, 2024)
Examining the interplay between choline chloride (ChCl) and ethylene glycol (EG) in Deep Eutectic Solvents (DES) assumes a pivotal role in designing innovative solvents. According to the literature, the comprehensive analysis of all possible types of conformers of ChCl and EG-based DES was scarce at different ratios, highlighting a gap in understanding at the atomistic level. In this study, we address this gap through a detailed Density Functional Theory calculation with dispersion correction (DFT+D3). Employing Density Functional Theory (DFT) calculations, our investigation delves into intermolecular relationships within DES, particularly focusing on ChCl and EG-based DES. DFT outcomes highlight the 1:2 ChCl to EG based DES ratio as notably more stable than alternative conformers. Key interactions within this DES conformation include: i) choline-chloride charge centers, ii) choline-EG links, and iii) EG-chloride anion associations. These findings provide valuable insights for crafting advanced solvents with tailored attributes. The intricate intermolecular interplay demonstrated here offers a versatile framework for harnessing DES potential across various domains, from chemical engineering to sustainable technologies.
Keywords: Density functional theory; Intermolecular force; Eutectic system; Hydrogen bond; Materials science; Chemical physics; Computational chemistry; Chemistry; Thermodynamics; Molecule; Physics; Organic chemistry; Composite material; Microstructure; type of access: open access